Children's use of transitional objects in pediatric healthcare settings: policies and practices - Leitner, Katelyn S. (East Carolina University, 2016)
Children experience medical interventions and hospitalizations every day. These settings are often characterized as strange and unfamiliar for children, may require some separations from established attachment figures, and have the potential to be extremely stressful. Many children turn to transitional objects such as soft stuffed animals or blankets to facilitate comfort in these environments, as these objects soothe and calm children when they are experiencing anxiety-like symptoms. Child life specialists work as a part of multidisciplinary healthcare teams, with a central role of identifying effective coping strategies for children who are experiencing stress. For many children, this coping mechanism may be the use of a transitional object. Currently, there is limited research examining children's use of transitional objects in healthcare settings or how child life specialists advocate for children's use of transitional objects in healthcare settings. The purpose of this study was to examine how child life specialists advocate for the use of transitional objects in pediatric healthcare settings. Using an exploratory design, the current study explored the current policies in medical settings that guide the use of transitional objects, as well as the practices of child life specialists when they encounter a child with a transitional object. Participants answered questions about how the policies at their setting are created, questions about their level of knowledge about transitional objects, and situational questions regarding their practices with transitional objects. Responses from 24 participants were analyzed through descriptive statics and thematic analysis. Results of the study revealed that only five of the 24 participants reported that their setting did not have any policies guiding the use of transitional objects. The majority of participants (n= 14) reported that they felt mostly knowledgeable about transitional objects, the majority of participants (n= 21) also believed transitional objects to be extremely important in stressful settings. Overall, participants revealed that they were willing to advocate for children's need to have access to transitional objects in healthcare settings.
Keywords: child life; Child health services; Transitional objects (Psychology); Child mental health; Attachment behavior in children